Areas of endemism in the Neotropical region based on the geographical distribution of Tabanomorpha (Diptera: Brachycera) - Klassa, Bruna; Santos, Charles Morphy D. (Zootaxa, 2015)
We aim to investigate the geographical distribution patterns of the infraorder Tabanomorpha and to delimit primary hypotheses of areas of endemism for the group in the Neotropical region. The results were compared to areas of endemism proposed in previous works for other taxa and particularly with the recent Morrone’s regionalisation proposal. An endemicity analysis was performed with the ndm/vndm algorithm using 3826 occurrence records for 1361 species of Tabanomorpha. Areas of endemism were established based on a grid size of 6º and consensus cut-off of 42%. We identified 13 areas of endemism comprising five main components: Northern South America (NSA), Southeastern South America (SESA), Central America (CA), Brazilian Savannah (BS), Central Andes (CAn). In a broad sense, the main areas of endemism recovered for Tabanomorpha are congruent with the recent proposals of regionalisation for the Neotropical region.